Effects of Premature Harvesting on Grain Weight and Quality: A Field Study - Xiao Zhang; Linsheng Yang; Zhong Li; Debao Tu (Agronomy)
Premature harvesting is a prevalent concern in rice cultivation, significantly impacting both grain yield and quality. However, there is limited information regarding the specific effects of premature harvesting on rice quality, particularly in terms of taste value. Consequently, this research aimed to assess the distribution of rice maturity and its implications for rice quality. A comprehensive study was conducted, comprising a one-year survey study and two years of field experiments, to examine the effects of premature harvesting on head rice rate, taste value, amylose content, and protein content. In the survey study, the results indicated that, on average, more than one-quarter of the samples exhibited a green rice rate exceeding 10% at harvest, with the majority having rates surpassing 15%. Premature harvesting was found to significantly reduce grain weight, head rice rate, and taste value, especially when the green rice rate exceeded 15%. Similarly, research experimentation demonstrated that premature harvesting significantly decreased the head rice rate and taste value, accompanied by a reduction in amylose content and an increase in protein content. The head rice rate (r = −0.148 **, p < 0.01), taste value (r = −0.217 **, p < 0.01), amylose content (r = −0.854 **, p < 0.01), and protein content (r = 0.475 **, p < 0.01) exhibited significant correlations with the green rice rate. These findings indicated that optimizing the harvest date is crucial to achieving a low green rice rate (<15%), thereby ensuring high head rice rate, taste value, and amylose content, along with low protein content.